Yellow Nail Syndrome: Dystrophic Nails, Peripheral Lymphedema and Chronic Cough - Christian Dornia; Ursula Johst; Tobias Lange; Sabine Käb; Okka Wilkea Hamer (Canadian Respiratory Journal)
A case involving a 41-year-old man with yellow nail syndrome (YNS) is reported. YNS is a rare disorder characterized by yellow, dystrophic nails, peripheral lymphedema and bronchiectasis with recurrent lower respiratory tract infections. YNS is often misdiagnosed because the syndrome is not well known. An interdisciplinary approach is required to recognize and collate the components of the syndrome accurately. Correct diagnosis is of utmost clinical importance because YNS can occur secondary to malignancies and autoimmune disorders. Hence, the diagnosis of YNS must prompt further investigation.